2021
DOI: 10.1507/endocrj.ej20-0808
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fenofibrate therapy on serum uric acid concentrations: a review and meta-analysis

Abstract: Fenofibrate is a marketed fibric acid derivative for lipid-lowering in patients with lipid disorders. Numerous studies have proven fenofibrate had a certain effect on serum uric acid, here we conducted this study to quantitatively assess the effect of fenofibrate intervention in modulating serum uric acid concentration and the influence on serum creatinine. The PubMed, Embase and Cochrane were systematically searched for randomized controlled trials update to January, 2020. Primary endpoints focused on serum u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…One of fibrates, fenofibrate, decreased serum UA levels by increasing its urinary excretion, most likely through the inhibition of URAT1 by fenofibric acid, its major metabolite [ 57 ]. The meta-analyses showed a significant reduction in plasma UA concentrations following fenofibrate therapy [ 58 , 59 ]. However, reduction of serum UA by pemafibrate was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…One of fibrates, fenofibrate, decreased serum UA levels by increasing its urinary excretion, most likely through the inhibition of URAT1 by fenofibric acid, its major metabolite [ 57 ]. The meta-analyses showed a significant reduction in plasma UA concentrations following fenofibrate therapy [ 58 , 59 ]. However, reduction of serum UA by pemafibrate was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Feno-F significantly reduced serum UA and further lowered plasma TG levels. [7] However, a few reports suggested that conventional fibrates may be associated with the risk of increased sCr levels. [9,10] In the present study, we confirmed that both Beza-F and Feno-F induced eGFR reduction even when administered at low doses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to lowering plasma TG levels, Feno-F significantly reduced serum uric acid (UA). [7] Moreover, treatment with Feno-F significantly improved arterial endothelial function. [8] Furthermore, a few studies have reported an increase in serum creatinine (sCr) during fibrate therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The mean 0.07 mmol/L serum urate reduction after 1 week of fenofibrate in our participants was close to the 0.06 mmol/L mean decrease after 6 weeks of treatment in a large clinical trial in type 2 diabetes 10 and the 0.08 mmol/L reduction in a metanalysis. 3 when there is hypertriglyceridaemia and/or retinopathy, 11 would thus have the added benefit of lowering serum urate. The pharmacodynamic effects of allopurinol are complex, but the dose required to achieve a serum urate of less than 0.36 mmol/L from the mean baseline level in our participants (0.43 mmol/L) is 125 mg daily.…”
Section: Discussionmentioning
confidence: 99%